THE SYSTEM OF COLLECTION AND DISPOSAL OF HOUSEHOLD MEDICAL WASTE: CURRENT STATE, LEGAL REGULATION AND PROSPECTS OF IMPLEMENTATION IN THE REPUBLIC OF KAZAKHSTAN - Aytkazin Ерлан Майданулы; Ibragimova Флюра Галимовна; Razieva Динара Багдатовна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
The article is devoted to the study of the problem associated with the uncontrolled release of household pharmaceutical waste accumulated from expired or unused medicines. The authors conducted a review of foreign experience in its legal support, referring to the need to introduce a new method of waste management in the country, in particular, a system for collecting and disposing of household medical waste, which is successfully available in the world, which will reduce environmental damage from these wastes. The existing systems of collection and disposal of household medical waste in European countries are analyzed in depth as successful samples. The authors propose to adopt a special law for the successful implementation of the system and regulation of its functioning and to amend and supplement the codes on the environment and the health of the people and the country’s health system. In addition, the authorized bodies consider that the draft law, which should be revised and developed by some regulatory acts, should contain a certificate on household medical waste, be established by the participating entities, and consolidate their rights and obligations. As a result of the study, the authors concluded that this change is necessary today, given that the implementation of the system in the country and its legal support require measures and resources that must be implemented at a large-scale state level. Therefore, taking into account the need to implement the state policy pursued in these areas, the principles of environmental protection and sustainable development, it is concluded that the time has come, together with government agencies, non-governmental organizations and other parties, to bring the issue to public discussion.